2020
DOI: 10.1016/j.nbd.2020.105119
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease uncovers an underlying sensitivity of subthalamic nucleus neurons to beta-frequency cortical input in vivo

Abstract: Abnormally sustained beta-frequency synchronisation between the motor cortex and subthalamic nucleus (STN) is associated with motor symptoms in Parkinson's disease (PD). It is currently unclear whether STN neurons have a preference for beta-frequency input (12-35 Hz), rather than cortical input at other frequencies, and how such a preference would arise following dopamine depletion. To address this question, we combined analysis of cortical and STN recordings from awake human PD patients undergoing deep brain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…Surrogate estimates from time-reversed signals were subtracted to normalize the resulting timefrequency estimates while reducing the impact of measurement noise. 22 A previously reported cortico-subthalamic driving of beta oscillations 23 is visible throughout all conditions with an appreciable but temporally inconsistent difference between OFF therapy and ON levodopa states at end of baseline resting period (−2 s; Figure 3A). At the time of motor intention, the ON levodopa condition was associated with a significant cluster of cortico-subthalamic coupling in the theta band (4-10 Hz; peak significance at 7 Hz, −0.9 s, P≤0.05 cluster corrected) when compared to the OFF therapy condition (Figure 3C,E).…”
Section: Dopaminergic Medication and Stn-dbs Shift Cortico-subthalami...mentioning
confidence: 67%
See 3 more Smart Citations
“…Surrogate estimates from time-reversed signals were subtracted to normalize the resulting timefrequency estimates while reducing the impact of measurement noise. 22 A previously reported cortico-subthalamic driving of beta oscillations 23 is visible throughout all conditions with an appreciable but temporally inconsistent difference between OFF therapy and ON levodopa states at end of baseline resting period (−2 s; Figure 3A). At the time of motor intention, the ON levodopa condition was associated with a significant cluster of cortico-subthalamic coupling in the theta band (4-10 Hz; peak significance at 7 Hz, −0.9 s, P≤0.05 cluster corrected) when compared to the OFF therapy condition (Figure 3C,E).…”
Section: Dopaminergic Medication and Stn-dbs Shift Cortico-subthalami...mentioning
confidence: 67%
“…Beta oscillations and their coupling have been proposed to signal the maintenance of a "status quo" that is suppressed by behavioral, motor and cognitive state changes 34 . Cortex drives beta activity in the basal ganglia, which can develop a vulnerability to beta hypersynchrony in the absence of dopamine 12 . An impactful rodent study has demonstrated this vulnerability in individually identified striatal medium spiny neurons in vivo in a dopaminergic lesion model of PD 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In rodent PD models, indirect pathway SPN exhibited pathological synchronization ( Sharott et al, 2017 ) and a hyperresponsiveness to cortical and thalamic stimulation ( Escande et al, 2016 ) while spiking activity in the down-stream entopeduncular nucleus (EPN, mouse analogue to human GPi) were abnormally correlated with STN hyperactivity ( Aristieta et al, 2019 ). In addition, pathological changes in this indirect pathway likely increases the sensitivity of the STN to beta frequency activation ( Baaske et al, 2020 ). Combining optogenetics with juxtacellular recordings in PD rats has been used to identify the GP as a critical hub driving pathological spiking patterns and synchronization within basal ganglia networks ( Crompe et al, 2020 ).…”
Section: Neural Recording Techniquesmentioning
confidence: 99%